The Titles’ Poetics of Max Kidruk’s Prose Works (Linguostylistic Studies, 2022)
The article highlights the main features of the titles’ poetics of Max Kidruk’s prose works. The emphasis is laid on the indisputable interconnection of the titles of all his artistic and journalistic texts with the author’s worldview and individual style, with the content of the works and their imagery. The uniqueness of the Max Kidruk works’ titles lies primarily in the fact that their appearance always precedes the writing of the text itself. And that’s why titles vividly reproduce the particular intention of the author. They are a starting point of the creation of each new text, an element of the integrity and perfection of a literary work, a personal sign of the author’s creativity, the basis for understanding the meaning of every particular artistic discourse, and perceiving his creative energy. They are a motivating tool in the reader’s choice of a book.The complex method of analysis of the case study material made it possible to reveal the entire range of main functions of the titles in Max Kidruk’s texts, in particular, nominative, motivational, and persuasive functions. The method of linguistic stylistic observation and contextual analysis made it possible to determine the motivational prerequisites for the creation of each title. Among them are the author’s personal lecturing activity, passion for travel, knowledge of typological structural-semantic and semantic patterns of constructing a title, genre heterogeneity of texts, and individual authorial features. The focus of the case study is on the traditional model of the syntactic organization of such a title as Love and Piranha, on the structural similarity of the titles Don’t Look Back and Be Silent and Look into My Dreams, and on the thematic cycle of titles, the supporting lexeme in which are geographical names (Mexican Chronicles, The Obsessed in Peru, To Zealand, Journey to the Navel of the Earth). The titles of Max Kidruk’s texts are distinguished by the originality of the structural and semantic organization, and, therefore, they distinctly manifest his individual style features.
Keywords: title of the artistic text; semantics; author; text; individual style